2022
DOI: 10.1097/ee9.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fine particulate matter exposure, habitual exercise, and dyslipidemia: A longitudinal cohort study

Abstract: What this study adds• This is the first large-scale cohort study investigating the combined effects of habitual exercise and chronic exposure to fine particulate matter (PM 2.5 ) on dyslipidemia. • Increased levels of exercise and reduced exposure to PM 2.5 are associated with a lower incidence of dyslipidemia. • Although the association between habitual exercise and dyslipidemia is slightly attenuated by PM 2.5 exposure, the negative associations between dyslipidemia and habitual exercise remains, regardless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The enhanced systemic and hepatic lipid metabolism prior to xenobiotics stimulation upon NMN treatment might confer mice with resistance to lipid accumulation caused by acute oxidative stress. Although it has been reported that prolonged oxidative stress and pro-inflammatory cytokines secreted from the lung triggers dyslipidemia, hepatic lipid accumulation, and subsequent extra-pulmonary injury, 56 , 57 it is unclear whether NMN intervention leads to attenuation in PM-induced inflammation through the modulation of lipid metabolism. Our results revealed that NMN supplementation effectively lowered the proportions of recruited and activated MDSCs and prevented profibrotic phenotype differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced systemic and hepatic lipid metabolism prior to xenobiotics stimulation upon NMN treatment might confer mice with resistance to lipid accumulation caused by acute oxidative stress. Although it has been reported that prolonged oxidative stress and pro-inflammatory cytokines secreted from the lung triggers dyslipidemia, hepatic lipid accumulation, and subsequent extra-pulmonary injury, 56 , 57 it is unclear whether NMN intervention leads to attenuation in PM-induced inflammation through the modulation of lipid metabolism. Our results revealed that NMN supplementation effectively lowered the proportions of recruited and activated MDSCs and prevented profibrotic phenotype differentiation.…”
Section: Discussionmentioning
confidence: 99%